Studi Takhrij dan Syarah Hadis tentang Akhlak - Ima Nurhalimah (Gunung Djati Conference Series, 2023)
This study aims to discuss the hadith about morals. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about morality in the history of Ahmad No. 23460. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi meets the maqbul qualifications for Islamic practice. This study concludes that the hadith narrated by Ahmad No. 23460 is relevant as a basis for fostering the morals of the younger generation in the country.